Attitudes, Norms, and the Effect of Social Connectedness on Adolescent Sexual Risk Intention. (9th July 2017) - Cederbaum, Julie A.; Rodriguez, Aubrey J.; Sullivan, Kathrine; Gray, Kandice
ABSTRACT: BACKGROUND: Risky sexual behaviors put adolescents at increased risk of adverse outcomes. Parents, school‐based adults, and peers play important roles in influencing these sex intentions. METHODS: This work explored the influence of parent‐child sex communication on adolescent attitudes, perceived norms, and intentions to have sex, including the moderating role of social support from school‐based adults, in a sample of 21, 731 adolescents in California. RESULTS: Although increased parent‐child sex communication was associated with intentions to have sex, it also exhibited protective effects, increasing abstinence attitudes among youth that led to decreased intention directly and via support from school‐based adults. CONCLUSIONS: Although many factors influencing sexual behaviors are largely intrapersonal, these findings indicate the importance of an ecological approach to reducing adolescent sexual risk behaviors through engagement of parents and increased school connectedness.